Prenatal antibiotic therapy as a risk factor for Neonatal Necrotizing Enterocolitis - L. G. Bochkova (Detskie Infekcii (Moskva), 2021)
The aim of this study was to determine whether there is an association between antenatal antibi-otic exposure and the incidence of necrotizing enterocolitis (NEC) in low birth weight infants.Study design: A retrospective case-control study was conducted on all infants with NEC who were born between 201 0 and 2020. Medical histories of all infants diagnosed with NEC ≥ Bella IIA stage and corresponding controls without NEC were examined. Maternal and newborn char-acteristics were compared using the Cochran-Mantel-Haenszel method, and logistic regression models were constructed to account for bias.Results. Clinical data were analyzed for 97 matched pairs. The adjusted odds ratio (OR) for pre-natal ampicillin exposure was significantly higher for infants who developed NEC (OR 2.3, 95% CI 1.1,4.8, P = 0.003) than for children in the control group. Infants who developed NEC were more likely to have a history of intrauterine exposure to ampicillin in the immediate prenatal period than infants who did not develop NEC.